OsPhyB-Mediating Novel Regulatory Pathway for Drought Tolerance in Rice Root Identified by a Global RNA-Seq Transcriptome Analysis of Rice Genes in Response to Water Deficiencies - Yoo, Yo-Han; Nalini Chandran, Anil K.; Park, Jong-Chan; Gho, Yun-Shil; Lee, Sang-Won; An, Gynheung; Jung, Ki-Hong (Frontiers in Plant Science, 2017)
Water deficiencies are one of the most serious challenges to crop productivity. To improve our understanding of soil moisture stress, we performed RNA-Seq analysis using roots from four-week-old rice seedlings grown in soil that had been subjected to drought conditions for 2 to 3 d. In all, 1098 genes were up-regulated in response to soil moisture stress for 3 d, which causes severe damage in root development after recovery, unlikely that of 2 d. Comparison with previous transcriptome data produced in drought condition indicated that more than 68% of our candidate genes were not previously identified, emphasizing the novelty of our transcriptome analysis for drought response in soil condition. We then validated the expression patterns of two candidate genes using a promoter-GUS reporter system in planta and monitored the stress response with novel molecular markers. An integrating omics tool, MapMan analysis, indicated that RING box E3 ligases in the ubiquitin-proteasome pathways are significantly stimulated by induced drought. We also analyzed the functions of 66 candidate genes that have been functionally investigated previously, suggesting the primary roles of our candidate genes in resistance or tolerance relating traits including drought tolerance (29 genes) through literature searches besides diverse regulatory roles of our candidate genes for morphological traits (15 genes) or physiological traits (22 genes). Of these, we used a T-DNA insertional mutant of rice phytochrome B (OsPhyB) that negatively regulates a plant’s degree of tolerance to water deficiencies through the control of total leaf area and stomatal density based on previous finding. Unlike previous result, we found that OsPhyB represses the activity of ascorbate peroxidase and catalase mediating ROS processing machinery required for drought tolerance of roots in soil condition, suggesting the potential significance of remaining uncharacterized candidate genes for manipulating drought tolerance in rice.